Central nervous system anomalies in craniofacial microsomia: a systematic review. Issue 1 (January 2018) - Renkema, R.W.; Caron, C.J.J.M.; Wolvius, E.B.; Dunaway, D.J.; Forrest, C.R.; Padwa, B.L.; Koudstaal, M.J.
Abstract: Extracraniofacial anomalies, including central nervous system (CNS) anomalies, may occur in craniofacial microsomia (CFM). This systematic review was performed to provide an overview of the literature on the prevalence and types of CNS anomalies and developmental disorders in CFM, in order to improve the recognition and possible treatment of these anomalies. A systematic search was conducted and data on the number of patients, patient characteristics, type and prevalence of CNS anomalies or developmental delay, and correlations between CFM and CNS anomalies were extracted. Sixteen papers were included; 11 of these described developmental disorders. The most common reported anomalies were neural tube defects, corpus callosum agenesis or hypoplasia, intracranial lipoma, Arnold–Chiari malformations, hydrocephaly, ventriculomegaly, and cerebral hypoplasia. The prevalence of CNS anomalies in CFM varied from 2% to 69%. The prevalence of developmental disorders, such as intellectual disability, language or speech developmental delay, and neuropsychomotor delay, varied from 8% to 73%. This study suggests that CNS anomalies and developmental disorders are seen in a substantial proportion of patients with CFM. Further research should focus on determining which features of CFM are correlated with CNS anomalies to allow adequate screening and timely care.